A meta-analysis of virtual reality training programs. (August 2021) - Howard, Matt C.; Gutworth, Melissa B.; Jacobs, Rick R.
Abstract: Virtual reality (VR) is the three-dimensional digital representation of a real or imagined space with interactive capabilities. The application of VR for organizational training purposes has been surrounded by much fanfare; however, mixed results have been provided for the effectiveness of VR training programs, and the attributes of effective VR training programs are still unknown. To address these issues, we perform a meta-analysis of controlled experimental studies that tests the effectiveness of VR training programs. We obtain an estimate of the overall effectiveness of VR training programs, and we identify features of VR training programs that systematically produce improved results. Our meta-analytic findings support that VR training programs produce better outcomes than tested alternatives. The results also show that few moderating effects were significant. The applied display hardware, input hardware, and inclusion of game attributes had non-significant moderating effects; however, task-technology fit and aspects of the research design did influence results. We suggest that task-technology fit theory is an essential paradigm for understanding VR training programs, and no set of VR technologies is "best" across all contexts. Future research should continue studying all types of VR training programs, and authors should more strongly integrate research and theory on employee training and development. Highlights: We perform a meta-analysis of controlled experimental studies that assesses VR programs for education and training. VR programs produce better outcomes than tested alternatives. Few moderating effects were significant, including the display hardware, input hardware, and inclusion of game elements. The task-technology fit of the VR training program, however, was a very strong moderator.